The Effects of Women’s Health Nursing Section Team Based Learning on Self-Directed Learning Ability, Learning Attitude and Problem Solving Ability - Cha Mi-Youn (Journal of Management Practices, Humanities and Social Sciences, 2018)
This study aims to develop a Section Team Based Learning (STBL) program for women health nursing education for undergraduate nursing students. It also intends to investigate the effects of the STBL on self-directed learning ability, learning attitude and problem solving ability. The participants(n = 69) were 34 people in an experimental group and 35 in a control group. A quasi-experimental nonequivalent control group pre/post-test design was used. Data were collected from the experimental group and the control group between September and October of 2017. This study was performed after obtaining approval by IRB (Institutional Review Board) and an agreement by the objects. The women's health nursing STBL program was operated by a researcher personally and run for 50 minutes per week over six weeks in total. It measured self-directed learning ability, learning attitude and problem solving ability of the participants before and after the program. As a result, it has shown that the STBL program exerted a significant influence on the problem solving ability for women health nursing learning (p < 000), but not on the self-directed learning ability and the learning attitude. Therefore, college education courses seem to need to be supplemented in order to foster outstanding and problem solving nursing resources. The women's health nursing STBL program will be helpful to improve problem solving ability of nursing students rather than a lecture class. It will also increase self-learning ability of the nursing students.